Topic- Evaluating Changes in Women’s Economic Empowerment in Pre and Post-SHG Joining: Role of Jeevikain Kaimur district of Bihar (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
The economic empowerment of women has emerged as a critical component of development strategies worldwide, particularly in rural areas where gender disparities persist. In this context, Self-Help Groups (SHGs) have gained prominence as vehicles for fostering women's economic autonomy and social empowerment. This study examines the Jeevika program's effect on financial empowerment among women in the Kaimur district, Bihar. Analyzing pre and post-SHG joining, it explores whether Jeevika can catalyze positive transformations for women and communities.For this purpose, the researcher used the exploratory and cross-sectional research design and based the study on primary data collected with the help of a structured questionnaire. Data was collected from a sample of 230 Self-Help Group women using a purposive sampling technique. The collected data was analyzed using frequency analysis and paired t-tests with the help of SPSS version 25. Based on the results, we rejected the null hypothesis (H0) for all 16 variables, indicating a statistically significant difference between women's perspectives before and after joining an SHG.